Kualitas, Kepuasan, Perawat KUALITAS KEHIDUPAN KERJA DAN KEPUASAN KERJA PERAWAT DI RUMAH SAKIT: QUALITY OF NURSING WORK LIFE AND WORK SATISFACTION IN HOSPITALS - Rahmawati, Ike Nesdia (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2017)
Abstract Quality of nursing work life (QNWL) and job satisfaction has been found to influence turnover intention of health professionals. Reliable information about the association of QNWL and job satisfaction of nurses were limited. The purpose of this study was to examine the relationships between QNWL and job satisfaction. This study used explanative cross sectional survey design. 32 nurses working at different units in hospital were selected by simple random sampling. PLS were used to analyze the data. Results showed that QNWL significantly associated with job satisfaction. Improving QNWL can be used to determine a strategy for improving job satisfaction. Keywords: nursing, quality, work-life, satisfaction, management